Ethics of the Eugenic - اسماعيل, عفراء; رجب , ريم (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The Eugenics movement returns to energe again with a new face threating the human kind, the ultration and change of man genetical matter search to creat persons enjoying in better health, far of dangerous diseases, and aiming for increasing the progen of best and birth control of worst even if that was by killing him. At the first this movement was a call for improving human life by termainiting poverty and illness then it became a new eugenical case armed with a progesive modern science, aiming to procreat a new man, happier, more intelligant and lives longer. In this research we seek to present an analytical study of this important issue, trying to discuss its dangerous effects on the future of humanity.